ANALISIS PENGARUH RASIO KEUANGAN RISK BASED CAPITAL DAN EARLY WARNING SYSTEM TERHADAP FINANCIAL SOLVENCY PADA PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA - Muhammad Rofiudin; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This research was conducted to analyze the effect of Risk Based Capital and the Early Warning System Ratio on Financial Solvency at Sharia Life Insurance Companies in Indonesia. The sample in this study was a Sharia Life Insurance service company that is already on the OJK list and published financial reports in the research period, namely 2015 - 2017. The analytical technique used was Multiple Linear Regression using SPSS 20 For Windows software. Based on the results of hypothesis testing. Simultaneous test results concluded that simultaneously the RBC and EWS variables in which there is a ratio of claim expenses, surplus changes, liquidity ratio, management cost, and premium growth ratio affects the Financial Solvency. The partial test results show that the surplus changes ratio, Claim Load Ratio, and Risk Based Capital does not affect Financial Solvency. While the management cost ratio, Liquidity Ratio and Influential Growth of Influence on Financial Solvency.Keywords    :Risk Based Capital and Early Warning System ratio, Financial Solvency.